Knowledge Representation for Legal Document Summarization (International Journal of Innovative Research in Computer Science & Technology, 2023)
This paper presents a novel approach for  legal document summarization. Proposed approach is based  on Ripple-Down Rules (RDR). It is an incremental  knowledge acquisition method. RDR allows us to quickly  build extendable knowledge base using classification rules.  The classification rules are written using a set of features.  Summary is generated using the identified rhetorical roles  in the document. Experiments demonstrate that the RDR  based Legal Document summarization approach  outperforms the supervised and unsupervised machine  learning models.
Keywords: Ripple-Down-Rules; Rhetorical Roles; Legal Document Summarization